Is thyroid disease associated with post-operative complications after total joint arthroplasty? A systematic review of the literature - Stavros Tsotsolis; Eustathios Kenanidis; Vasileios F Pegios; Michael Potoupnis; Eleftherios Tsiridis (EFORT Open Reviews, 2023)
• Background: This comprehensive systematic review aims to assess the literature regarding the risk of postoperative complications in patients undergoing total joint arthroplasty (TJA) with concomitant thyroid dysfunction. • Methods: Studies were identified by searching PubMed, Cochrane Central Register of Controlled Trials (CENTRAL), Scopus, and ClinicalTrials.gov (end of search: May 2022). • Inclusion criteria: Randomized control and case-control studies, cohort and observational clinical studies were included, which focused on postoperative complications and outcomes of patients undergoing TJA operations of major joints (knee, hip, ankle, elbow). All studies were assessed according to their level of evidence, the number and age of patients, and treatment complications. • Analysis: Nine studies were included in this review that demonstrated a higher risk of postoperative anemia, perioperative blood loss, hemoglobin decrease, and transfusion rates in hypothyroid patients after TJA. • Results: Hypothyroidism has been identified as a potential but modifiable risk factor for increased rates of deep venous thrombosis, acute kidney injury, pneumonia, and non-specified cardiac complications among hypothyroid patients who underwent TJA as well as increased rates of periprosthetic joint infection. No significant differences in the prosthesis-related mechanical complication rates have been calculated when comparing hypothyroid and euthyroid patients. ture surgeons.